Social workers' perception of practice with lesbians, gays and bisexuals (LGBs) in Nigeria (Journal of Comparative Social Work, 2020)
People from Low-to-Middle-Income Countries (LMICs) like Nigeria, irrespective of differences in beliefs and sexual orientation, face similar challenges in terms of living standards, access to resources and quality of life. However, people who have been ‘othered’ on the basis of their nonconformity to heteronormativity face additional challenges. The existence of the Same-Sex Marriage (Prohibition) Act (SSMPA) of 2014, which criminalizes the normalization of homosexual ‘lifestyles’ and the persistence of a homophobic socio-political climate in Nigeria, exposes lesbians, gays and bisexuals (LGBs) in Nigeria to unique difficulties. Although social workers are expected to work, guided by the values of social justice and respect for human rights, with the vulnerable and oppressed in society such as LGBs, the socio-political contexts they operate in can limit how well they do this work. This paper seeks to explore the views of social workers on social work practice with LGBs in Nigeria, with qualitative data obtained from 12 professional social workers using in-depth interviews that were thematically analysed. Findings show that social workers’ perception of practice with LGBs in Nigeria is influenced by existing policies in the country, in addition to cultural and religious beliefs. Some social workers also view LGBs through a medical perspective of homosexuality being an illness, which can affect their work with this population. Recommendations from the study include developing a contextualized ethical code that addresses practice dilemmas and further research centred on the experiences of LGBs and social work practice, as this is one of the few studies on social work practice in Nigeria with this population.